Voroshilov talking with veterans of the war with Turkey (1877) on occasion of the commemoration of the 5th anniversary of the the liberation of Romania
Voroshilov talking with veterans of the war with Turkey (1877) on occasion of the commemoration of the 5th anniversary of the the liberation of Romania.